Principles of Mathematics in Operations Research - Kandiller, Levent. (International Series in Operations Research & Management Science,, 2007)
Principles of Mathematics in Operations Research is a comprehensive survey of the mathematical concepts and principles of industrial mathematics. Its purpose is to provide students and professionals with an understanding of the fundamental mathematical principles used in Industrial Mathematics/OR in modeling problems and application solutions. All the concepts presented in each chapter have undergone the learning scrutiny of the author and his students. The conceptual relationships within the chapter material have been developed in the classroom experience working with the students' level of understanding. The illustrative material throughout the book (i.e., worked-out problems and examples of the mathematical principles) was refined for student comprehension as the manuscript developed through its iterations, and the chapter exercises are refined from the previous year's exercises. In sum, the author has carefully developed a pedagogically strong survey textbook of OR and Industrial Mathematics.